2004
DOI: 10.1038/sj.onc.1207523
|View full text |Cite
|
Sign up to set email alerts
|

Toxic proteins released from mitochondria in cell death

Abstract: A plethora of apoptotic stimuli converge on the mitochondria and affect their membrane integrity. As a consequence, multiple death-promoting factors residing in the mitochondrial intermembrane space are liberated in the cytosol. Pro-and antiapoptotic Bcl-2 family proteins control the release of these mitochondrial proteins by inducing or preventing permeabilization of the outer mitochondrial membrane. Once released into the cytosol, these mitochondrial proteins activate both caspase-dependent and -independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
585
0
28

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 836 publications
(624 citation statements)
references
References 137 publications
11
585
0
28
Order By: Relevance
“…The mechanisms regulating the release of specific mitochondrial proteins during cell death are not completely understood (Donovan and Cotter, 2004;Henry-Mowatt et al, 2004;Saelens et al, 2004). Our data showed that A3D8 treatment induced loss of DCm and AIF release from mitochondria without cytochrome c release.…”
Section: Cd44-induced Cell Death In Erythroleukemia Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…The mechanisms regulating the release of specific mitochondrial proteins during cell death are not completely understood (Donovan and Cotter, 2004;Henry-Mowatt et al, 2004;Saelens et al, 2004). Our data showed that A3D8 treatment induced loss of DCm and AIF release from mitochondria without cytochrome c release.…”
Section: Cd44-induced Cell Death In Erythroleukemia Cellsmentioning
confidence: 73%
“…Key events in classic apoptosis as well as in other forms of cell death are the disruption of mitochondrial function and the release of apoptogenic proteins from the intermembrane space (IMS) of mitochondria (Henry-Mowatt et al, 2004;Saelens et al, 2004). Although the process of the mitochondrial outer membrane permeabilization (MOMP) is mainly controlled by the members of the Bcl-2 family, the exact mechanisms responsible of this process remain controversial (Donovan and Cotter, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Once relocalized to the cytosol, cytochrome c activates caspase-9 by binding its regulatory subunit Apaf-1, a AAA ATPase-related protein with a C-terminal WD repeat protein (Li et al, 1997;Yu et al, 2005). Additional pro-death factors that are released from mitochondria (e.g., AIF, SMAC/Diablo, Omi/Htr2A) were reported to activate both caspase-dependent and caspase-independent death programs, though controversies remain (Foghsgaard and Jaattela, 1997;Jaattela, 2002;Garrido and Kroemer, 2004;Saelens et al, 2004;Polster et al, 2005). This mitochondrial outer membrane permeabilization (MOMP) occurs by an unknown biochemical mechanism that requires one or both of the pro-death multidomain Bcl-2 family proteins Bax and Bak (Hardwick and Polster, 2002;Green and Kroemer, 2004).…”
Section: The Executioner Mitochondrionmentioning
confidence: 99%
“…5,6 Apoptosis occurs through two main signaling pathways: an extrinsic pathway that utilizes a diversified group of cell surface death receptors; [7][8][9][10][11][12][13][14] and an intrinsic pathway that utilizes various intracellular organelles to execute the programmed cell death machinery. [15][16][17][18][19][20] An important and well-studied point of control for both the extrinsic and intrinsic apoptotic pathways is the Bcl-2 family of proteins that comprise both pro-and antiapoptotic members and regulate the apoptotic program through a tightly controlled series of checks and balances. 21,22 Resistance to cell death is a common feature in many disease states that impedes both therapy and treatment.…”
mentioning
confidence: 99%